Research on flame retardant and smoke suppression technology of asphalt and its mechanism - Song, Yanxin; Liu, Peirong; Huang, Jinlong; Li, Beite; Li, Huangsheng (Frontiers in Built Environment, 2026)
As tunnel traffic infrastructure rapidly expands, the construction of asphalt pavements within tunnels and fire protection measures have become particularly critical. Asphalt, as a commonly used paving material, exhibits combustion characteristics and smoke suppression capabilities that are of paramount importance. This paper first examines the combustion of asphalt, outlining its fire retardant mechanisms. Subsequently, it categorizes and discusses asphalt fire retardant technologies, Explaining the various types of flame retardants and how each works. It further examines how incorporating flame-retardant components and using high-void pavement structures improve fire resistance. The study then addresses research methodologies for evaluating flame retardant performance, listing several testing methods and comparing their ability to assess relevant indicators of asphalt’s fire retardant efficacy. It highlights the limitations of relying on a single indicator in current research and the discrepancies that arise in practical engineering applications. The paper also summarizes the conditions for the currently popular nano-modified asphalts, outlining the parameters for some prevalent nano-modified asphalt formulations. This study highlights the dual role of nanomaterials in enhancing asphalt flame retardancy via char formation and catalytic oxidation, and in concurrently curbing VOC emissions. This work paves the way for developing novel, green, and high-performance asphalt materials. Finally, it concludes by summarizing the research trends and potential future directions for flame retardant asphalt, identifying areas that warrant further investigation.